Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1071/fp04123
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope composition and water-use efficiency in plants with crassulacean acid metabolism

Abstract: Abstract.The relationship between water-use efficiency, measured as the transpiration ratio (g H 2 O transpired g −1 above-plus below-ground dry mass accumulated), and 13 C / 12 C ratio (expressed as δ 13 C value) of bulk biomass carbon was compared in 15 plant species growing under tropical conditions at two field sites in the Republic of Panama. The species included five constitutive crassulacean acid metabolism (CAM) species [Aloe vera (L.) Webb & Berth., Ananas comosus (L.) Merr., Euphorbia tirucalli L., K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 47 publications
(54 reference statements)
3
67
0
7
Order By: Relevance
“…Determination of chlorenchyma cell sap titratable acidity during both the wet and the dry seasons indicated existence of diurnal acidificationÁdeacidification cycles denoting operation of the obligate CAM. This CAM physiotype has previously been reported in some stem succulent Euphorbia species (Pearcy & Troughton 1975;Willert et al 1985;Martin et al 1990;Van Damme 1991;Mies et al 1996;Elhaak et al 1997;Winter et al 2005;Ameh 2006;Feakins and Sessions 2010). Nocturnal CO 2 uptake and daytime stomatal closure characteristic of CAM imply avoidance of gas exchange when environmental conditions favor transpirational water loss and hence enhanced plant water economy (Walker & Leegood 1996;Winter & Smith 1996;Borland et al 2000;Sayed 2001b;Luttge 2004;Lu¨ttge 2008;Herrera 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Determination of chlorenchyma cell sap titratable acidity during both the wet and the dry seasons indicated existence of diurnal acidificationÁdeacidification cycles denoting operation of the obligate CAM. This CAM physiotype has previously been reported in some stem succulent Euphorbia species (Pearcy & Troughton 1975;Willert et al 1985;Martin et al 1990;Van Damme 1991;Mies et al 1996;Elhaak et al 1997;Winter et al 2005;Ameh 2006;Feakins and Sessions 2010). Nocturnal CO 2 uptake and daytime stomatal closure characteristic of CAM imply avoidance of gas exchange when environmental conditions favor transpirational water loss and hence enhanced plant water economy (Walker & Leegood 1996;Winter & Smith 1996;Borland et al 2000;Sayed 2001b;Luttge 2004;Lu¨ttge 2008;Herrera 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Average meteorological conditions at the study site during the experiment are shown in Table II. These values were calculated from data collected on site every 15 min by an automated weather station (Winter et al, 2001(Winter et al, , 2005. Seedlings of Cupressus lusitanica, Pinus caribaea, and Thuja occidentalis were obtained from a commercial nursery in Chiriqui Province, Republic of Panama.…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…By allowing CO 2 uptake at night when the evapotranspiration rates are lower, the CAM pathway brings about substantial water conservation and represents a considerable adaptive advantage for plants living in habitats characterized by seasonal or intermittent restrictions in water supply (Lü ttge, 2004;Winter et al, 2005).…”
mentioning
confidence: 99%